Inovasi Pengolahan Kripik Biji Durian sebagai Produk Bernilai Tambah - Humaidi; Qodir, Abd.; Aisyah, Siti; Agustian, M.; Aini, Masrurotul (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Jangkar Village, Tanah Merah Subdistrict, Bangkalan Regency, produces abundant durian seed waste every harvest season. Until now, this waste has only been discarded, potentially causing environmental problems. This community service activity aims to address this problem by developing durian seed chips as a value-added food innovation, which also creates micro-business opportunities based in the village. The methods used in this activity include situation analysis, technical training in chip processing, business management assistance, and marketing. Evaluation is carried out through consumer response testing using pre-test and post-test questionnaires. Product responsiveness testing was conducted on 42 respondents from the surrounding community (after the production process). The test results showed that most respondents (80%) liked the durian seed chips. The main reasons for liking them were their savory taste and crunchy texture, although the distinctive aroma of durian was considered less prominent. A comparison between the pre-test (before trying) and post-test (after trying) of the product showed a significant increase in interest in trying the product (from 55% to 85%), taste assessment (from 50% to 80%), texture appreciation (from 48% to 75%), and suitability as a marketable product (from 45% to 70%). The initial market test also received positive responses and enthusiasm from the community. The contributions of this activity include product innovation, improvement of community skills, additional income opportunities, and support for environmental preservation. Thus, durian seed chips have the potential to become a sustainable regional specialty product with promising market prospects